Nanoporous Au structures by dealloying Au/Ag thermal- or laser-dewetted bilayers on surfaces. (March 2017) - Ruffino, F.; Torrisi, V.; Grillo, R.; Cacciato, G.; Zimbone, M.; Piccitto, G.; Grimaldi, M.G.
Abstract: Nanoporous Au attracts great technological interest and it is a promising candidate for optical and electrochemical sensors. In addition to nanoporous Au leafs and films, recently, interest was focused on nanoporous Au micro- and nano-structures on surfaces. In this work we report on the study of the characteristics of nanoporous Au structures produced on surfaces. We developed the following procedures to fabricate the nanoporous Au structures: we deposited thin Au/Ag bilayers on SiO2 or FTO (fluorine-doped tin oxide) substrates with thickness xAu and xAg of the Au and Ag layers; we induced the alloying and dewetting processes of the bilayers by furnace annealing processes of the bilayers deposited on SiO2 and by laser irradiations of the bilayers deposited on FTO; the alloying and dewetting processes result in the formation of Aux Agy alloy sub-micron particles being x and y tunable by xAu and xAg . These particles are dealloyed in HNO3 solution to remove the Ag atoms. We obtain, so, nanoporous sub-micron Au particles on the substrates. Analyzing the characteristics of these particles we find that: a) the size and shape of the particles depend on the nature of the dewetting process (solid-state dewetting on SiO2, molten-state dewetting on FTO); b) the porosity fraction of the particles depends on how the alloying process is reached: about 32% of porosity for the particles fabricated by the furnace annealing at 900 °C, about 45% of porosity for the particles fabricated by the laser irradiation at 0.5 J/cm 2, in both cases independently on the Ag concentration in the alloy; c) After the dealloying process the mean volume of the Au particles shrinks of about 39%; d) After an annealing at 400 °C the nanoporous Au particles reprise their initial volume while the porosity fraction is reduced. Arguments to justify these behaviors are presented. Graphical abstract: Highlights: Au/Ag bilayers are deposited on SiO2 and FTO substrates. Furnace annealing and laser annealing processes are performed to form Aux Agy alloyed sub-micron particles. The Aux Agy alloyed particles are dealloyed to form Au nanoporous particles. The effect of a furnace annealing process on the Au nanoporous particles is studied. The porosity fraction of the Au nanoporous particles is quantified as a function of the fabrication processes parameters.